Women's empowerment and child nutrition: A propensity score matching analysis - Samwel Saimon Lwiza; Cresencia Apolinary Masawe (Nutrition and Health, 2026)
Background Child undernutrition remains a major public health challenge in Tanzania and other low- and middle-income countries. Although women's empowerment is recognized as a key determinant of child nutrition, evidence based on its multidimensional measures from nationally representative data remains limited. Aim This study examines the association between women's empowerment and the nutritional status of under-five children in Tanzania. Methods Data were drawn from 1790 children under-five years of age in the 2021/22 Tanzania National Panel Survey. Child nutritional outcomes; stunting, wasting, and underweight were measured using anthropometric z-scores based on World Health Organization child growth standards. A multidimensional women's empowerment index was constructed across instrumental, enabling , and collective agency domains. Propensity score matching and logistic regression models were employed to assess the association between women's empowerment and child nutritional outcomes. Summary Women's empowerment was significantly associated with reduced odds of wasting, with children of empowered women having 69% lower odds of acute malnutrition than those of disempowered women. Domain-specific analyses indicated that women's financial autonomy, work-life balance, and group membership were associated with improved child nutritional outcomes, while associations with stunting and underweight were less consistent. These findings suggest that strengthening women's financial autonomy, promoting balanced work responsibilities, and supporting women's participation in community groups may contribute to reducing child malnutrition. Integrating gender-responsive and nutrition-sensitive policies could help improve child nutritional outcomes in Tanzania.